Changes of Protein Composition in Membrane-Skeleton Complex of Erythrocytes Cryopreserved Under PEO-1500 Protection - Zemlyanskikh, Nina; Zubov, Pavlo; Babijchuk, Lubov (Problems of Cryobiology and Cryomedicine, 2007)
When investigating the modification of protein composition of membrane-cytoskeleton complex (MCC) of the erythrocytes cryopreserved under PEO-1500 protection the change of relative content of band 3 protein, ankyrin, protein 4.2 and protein 4.9 in the solutions with high ionic strength and variation of the content of bivalent cations was found. It has been noted that MCC changes in the erythrocytes cryopreserved with PEO-1500 and frozen with no use of cryoprotectants are characterized with some common features. This may be stipulated by the absence inside cells of the substances stabilizing the protein structure at low temperatures. Alterations in MCC of erythrocytes cryopreserved with PEO-1500 protection may be partially reversible if the cells are transferred into physiological conditions.